OPTIMAL LOSSES IN POWER DISTRIBUTION NETWORKS - M. I. Fursanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The distributed power network 0,38–10 kV is investigated and the conditions for providing optimal load of network and technically reasonable (minimal) values of electricity consumption are determined. It is shown that the optimum (minimum) value of all technical losses of electricity in power network 0,38–10 kV is being achieved at the equality of semi-constant and variable (load) losses in network  and in denominated units for the period T and is characterized by twice value of variable losses. Optimum work load of transformers is determined by their technical data and is equal to (approximately) 40 % and corresponds to relatively low value of minimum losses – 1,73 %. In the whole, in network 0,38–10 kV there is optimal load factor for non-changeable equipment set, to a great extent, which depends on configuration and type of equipment. The more branching of network the less will be effective line’s resistance and so the value of optimal load factor will be more significant.Networks 0,38 kV mainly influence on formation and value of total electricity losses in network 0,38–10 kV as losses in 0,38 kV networks under the equal conditions are higher than in 10 kV networks in times (or ten times). Losses in 0,38 kV network to a great extend decreases the value of generalized coefficient of network load and increases optimal value of relative loss in network 0,38–10 kV. And optimal total losses in denominated units are not changed. The developed structural algorithm of technical losses of electricity in network 0,38–10 kV allows evaluating actual and optimal network loading, to determine minimum and reserves of losses enhancement, but it can be realize only when loading of lines and transformers is low. That is why minimum technical losses are not finale criteria of optimal state of network which should be (in reality) determined from economical reasons, for example, from minimum cost of electrical energy transmission.